The Impact of Green Banking Adoption, Company Size, and Good Corporate Governance on the Profitability of Islamic Commercial Banks in Indonesia - Nisa Arista; Ahmad Zuliansyah; Is Susanto (Department of Islamic Banking, 2026)
Purpose – This study aims to analyse the effect of Green Banking implementation, Company Size, and Good Corporate Governance on the profitability of Islamic Commercial Banks in Indonesia for the period 2019–2024. Methodology – Quantitative research using panel data from six Islamic Commercial Banks through financial reports and sustainability reports. Analysis using Fixed Effect Model (FEM) panel data regression. Findings – Green Banking and GCG have a significant positive effect on ROA, while Company Size has no significant effect. Simultaneously, the three variables have no significant effect. Implications– This study can serve as a basis for the conclusion that the profitability performance of Islamic Commercial Banks is not primarily influenced by the scale of total assets, but is more determined by the effectiveness of Green Banking implementation and the quality of Good Corporate Governance practices. Originality– This study offers originality by integrating the variables of Green Banking, Company Size, and Good Corporate Governance into a single panel data model analysed from an Islamic economic perspective for the period 2019–2024.